How we diagnose Myelodysplastic syndromes - Oster, Howard S.; Mittelman, Moshe (Frontiers in Oncology, 2024)
The Myelodysplastic syndromes (MDS) are a heterogenous group of clonal bone marrow (BM) stem cell myeloid neoplasms, characterized by ineffective hematopoiesis that results in dysplasia in hematopoietic cells and peripheral cytopenias, especially anemia, and a propensity to leukemic transformation. The suspicion of MDS is raised by a typical but not specific clinical picture and routine laboratory findings, but the gold standard for MDS diagnosis is still BM examination with the presence of uni-or multi-lineage dysplasia and increased blast percentage, together with exclusion of other reasons. Cytogenetics is also an essential part of the diagnostic and prognostic processes. Flow cytometry and full genetic characterization are helpful but not mandatory for MDS diagnosis. This review summarizes the current steps of diagnostic approach for a patient suspected of having MDS. We also express our hopes that within the near future, non-invasive technologies, especially digital and peripheral blood genetics, will mature and be introduced into practice.